Na co všechno můžeme narazit? - Škodová, Svatava (Bohemistyka, 2021)
The article deals with the current use of the verb narazit na “to come across” in contemporary Czech. Based on examples from the Czech National Corpus, it analyses the types of collocations and points out their specifics. The analysis focuses on the non-primary, resp. abstract meanings of this verb.